Nematode-Mycobiota interactions in Pine Wilt Disease - Vicente, Cláudia (2022)
Pine wilt disease is one of the most important diseases for conifer forests worldwide. This complex disease involves the interaction between three primary biological elements - the plant parasitic nematode Bursaphelenchus xylophilus; the insect-vector Monochamus sp., and the host tree Pinus spp. – and other secondary elements such as endophytic bacteria and fungi. The development of B. xylophilus is strongly associated with fungi that colonize the declining trees, with special impact in their reproduction and number of individuals carried by the vector. In light of previous knowledge, we are focused in obtaining a detailed characterization of the structure and dynamics of the nematode-fungi interactions through culturable and non-culturable approaches with particular emphasis in metagenomics analysis. Our aim is to understand if nematode-associated mycobiota plays a key-role in the development of the disease, in interaction with nematode and insect-vector, and into which extend it can be used to disrupt the disease cycle.